Polymer electrolyte membranes based on PEO-containing block copolymers. Issue 1 (4th March 2021) - Kunitskaya, L.; Zheltonozhskaya, T.; Nesin, S.; Klepko, V.
Abstract: Triblock copolymers comprising chemically complementary poly(ethylene oxide)/polyacrylamide (TBC) and their partially hydrolyzed derivative (TBChydr ) were investigated as possible ion-conducting membranes for Li-ion batteries (LBs), dye-sensitized solar cells (DSSCs) and fuel cells (PEFCs). Two TBC samples consisting PEO blocks of variable block length (Mn PEO = 6·10 4 and 3.5·10 4 kDa) were synthesized and used for these purpose. It was noticed that ionic conductivity of TBC membranes increases with PEO block lengthening from 6.2·10 −11 to 3.2·10 −9 S⋅cm −1 . The introduction of additional ionic groups -COOH in polyacrylamide block of TBC has a positive effect on the conductive characteristics of copolymer membranes. The ionic conductivity of TBC membranes filled with LiPF6 increases with increasing of salt content.